Directed Technological Change and Energy Efficiency Improvements - Jan Witajewski-Baltvilks; Elena Verdolini; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper applies the Directed Technical Change (DTC) framework to study improvements in the efficiency of energy use. We present a theoretical model which (1) shows that the demand for energy is shifted down by innovations in energy intensive sectors and (2) highlights the drivers of innovative activity in these sectors. We then estimate the model through an empirical analysis of patent and energy data. Our contribution is fivefold. First, our model shows that under very general assumptions information about energy expenditures, knowledge spillovers and the parameters governing the R&D process are sufficient to predict the R&D effort in efficiency improving technologies. Second, we pin down the conditions for a log-linear relation between energy expenditure and the R&D effort. Third, the calibration of the model provides clear evidence that the value of the energy market as well as international and inter-temporal spillovers play a significant role in determining the level of innovative activity. Fourth, we show that innovative activity in energy intensive sectors shifts down the (Marshallian) demand for energy. Finally, we show that due to the streamlined modelling framework we adopt, the point estimates from our regression can potentially be used to calibrate any model of DTC in the context of energy consumption.
Keywords: O31; O33; Q43; 330; Energy Efficiency; Directed Technological Change; Induced Innovations; Patents Econometrics